Physical and profile data collected aboard the F.G. Walton Smith during cruise WS1202 in the Gulf of Mexico and North Atlantic Ocean from 2012-02-27 to 2012-03-02 (NCEI Accession 0129868) - Kelble, Christopher (NOAA NCEI Environmental Data Archive, 2015)
NODC Accession 0129868 includes physical and profile data collected aboard the F.G. Walton Smith during cruise WS1202 in the Gulf of Mexico and North Atlantic Ocean from 2012-02-27 to 2012-03-02. These data include CONDUCTIVITY, SALINITY and WATER TEMPERATURE. The instruments used to collect these data include CTD. These data were collected by Christopher Kelble of US DOC; NOAA; OAR; Atlantic Oceanographic and Meteorological Laboratory, and by Rosenstiel School of Marine and Atmospheric Science as part of NOAA South Florida Ecosystem Research and Monitoring Program. The Lamont-Doherty Earth Observatory (LDEO) submitted these data to NODC as part of the NSF sponsored Rolling Deck to Repository (R2R) program.